2019
DOI: 10.1177/0040517519832834
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach for human hand evaluation of split or large set of fabrics

Abstract: Assessment of fabric handle relies on the feel of humans. The precision of the results greatly depends on the size of the fabric sets. The precision decreases with increasing number of samples as a consequence of assessors' fatigue and loss of concentration. Given the importance of handle assessment and in the absence of guidelines that assist assessment of large sample sets, this study proposes a comprehensive approach for testing large sets of fabrics by dividing them into several testing sessions, each of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In the initial stage, 27 people were recruited, whereas 25 people fully participated. According to a prior study (Musa et al, 2019 ), women tend to have better sensitivity in touch than men. Therefore, only female participants were recruited.…”
Section: Methodsmentioning
confidence: 92%
“…In the initial stage, 27 people were recruited, whereas 25 people fully participated. According to a prior study (Musa et al, 2019 ), women tend to have better sensitivity in touch than men. Therefore, only female participants were recruited.…”
Section: Methodsmentioning
confidence: 92%
“…Our study had three main limitations. First, all participants were in their 20s, which may result in finger sensitivity bias related to differences based on age and may have thus affected the fabric hand test results (Musa et al. , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our study had three main limitations. First, all participants were in their 20s, which may result in finger sensitivity bias related to differences based on age and may have thus affected the fabric hand test results (Musa et al, 2019). Second, the results may have been affected by cross-cultural differences (both linguistic and perceptual) regarding the fabric hand descriptors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that judgments show no significant origin-, gender- or age-based differences in the subjective assessments. 23 The assessments were conducted in the standard condition by referring to the American Association of Textile Chemists and Colorists (AATCC) EP5-2007 evaluation procedure. The judges were trained to be acquainted with the descriptions and ranking scales for three typical tactile feelings before carrying out the assessments.…”
Section: Methodsmentioning
confidence: 99%